ANALISIS RISIKO K3 PADA PENGELOLAAN BAHAN KIMIA DENGAN METODE HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL (HIRARC) DI UPTD LABORATORIUM LINGKUNGAN DINAS LINGKUNGAN HIDUP TAHUN 2025 - Siregar, Ripai -; hasian, muhammad tsawaby (Jurnal Inovasi Kesehatan Masyarakat, 2025)
This study discusses occupational health and safety (OHS) risk analysis in chemical management at the Environmental Laboratory Unit of Asahan District. Using the HIRARC method, the study aims to identify hazards, assess risk levels, and determine control measures to prevent work accidents caused by exposure to hazardous chemicals in the laboratory. This research uses a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation. The analysis was carried out using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) approach to identify potential hazards, assess risk levels based on consequence and likelihood, and formulate appropriate risk control measures in the laboratory. The results showed various potential hazards in chemical management, such as corrosive, flammable, and toxic substances. Based on HIRARC analysis, several high-risk activities were found that require immediate control. Control recommendations include elimination, substitution, engineering controls, safe work procedures, and consistent use of personal protective equipment (PPE). The study concludes that chemical management in laboratories has a high risk to occupational safety. Continuous implementation of the HIRARC method is needed to identify and control hazards. Recommendations include enhancing OHS training, regular use of PPE, and improving work procedures and infrastructure to minimize potential accidents.